2018
DOI: 10.1080/00223891.2018.1475392
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorders, Personality Traits, and Grievance-Fueled Targeted Violence: The Evidence Base and Implications for Research and Practice

Abstract: This article aims to move away from intuitive appeals that link mental disorder with violence such as terrorism, mass murder, and other targeted violence. The article synthesizes the existing evidence base regarding the relationship between mental disorders and personality traits and (a) attitudinal affinities with violent causes, and (b) a number of violent behaviors (including mass murder and terrorism). The evidence base is mixed and the research focus changed across time: from simple and unempirical assert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 81 publications
1
36
0
Order By: Relevance
“…A core objective from the start was to 'improve the understanding of both police and health professionals of the associations between mental health conditions and vulnerability to radicalisation'. This was initiated after a research programme had identified 'a broad range of mental health and psychological difficulties' in around half of 657 Prevent referrals (NPCC, Undated; see also Corner et al, 2018b).…”
Section: Mental Health Hubsmentioning
confidence: 99%
“…A core objective from the start was to 'improve the understanding of both police and health professionals of the associations between mental health conditions and vulnerability to radicalisation'. This was initiated after a research programme had identified 'a broad range of mental health and psychological difficulties' in around half of 657 Prevent referrals (NPCC, Undated; see also Corner et al, 2018b).…”
Section: Mental Health Hubsmentioning
confidence: 99%
“…Because of this, psychologists researching, responding to, and trying to stop acts of mass violence often do not have access to perhaps the most important source of information, the attacker. Furthermore, as pointed out by Corner et al (2018), it might be difficult to obtain accurate information from sources who could be hostile, resistant, and distrustful, such as family members or individuals who share the goals and ideology of an attacker.…”
mentioning
confidence: 99%
“…A thread running through the papers written by Archer (2018), Corner et al (2018), Lankford (2018), and Meloy (2018) is the distinction between attempts to predict mass violent behavior and attempts to identify factors that alone or in combination increase the risk of violence. This reflects a shift from viewing terrorist attacks and mass shootings as stemming from a specific form of psychopathology, such as psychopathy, to viewing mass violence as the end result of a dynamic process that might be provoked by specific issues, such as a sense of grievance, mistreatment, or victimization, but not be acted on unless other factors, such as a desire for attention and fame, are present.…”
mentioning
confidence: 99%
See 2 more Smart Citations